A JUST TRANSITION FOR THE INDIGENOUS SAMI PEOPLE? A qualitative content analysis of the European Green Deal and the Critical Raw Materials Act - Carling, Lina (2024)
Current research has not studied how the EU’s environmental policy affects Sami people. This is all the more relevant to address since the effects on Sami people are critical to a just transition, which the European Green Deal is committed to create. To address this gap in the research, this study focuses on the nexus of indigenous rights and the EU just transition. The thesis aim is to show whether and how the EU’s environmental policy, focusing on the European Green Deal and the Critical Raw Materials Act, creates a just transition in relation to indigenous people. The study applies the just transition framework, which is based on the principles of distributional, procedural, recognitional, and restorative justice. Furthermore, the practical meanings of the justice principles are elaborated on in relation to indigenous rights, which informs the criteria used in the qualitative content analysis. The results indicate that the EU’s creation of a just transition does not sufficiently incorporate indigenous people, although it meets some of the necessary criteria for the justice principles. The thesis finds that the just transition created by the EU is more restricted in scope, rather than inclusive and just for all, focusing mostly on worker’s rights while the recognition of indigenous rights is inadequate.